Formation and control of disinfection by-products from iodinated contrast media attenuation through sequential treatment processes of ozone-low pressure ultraviolet light followed by chlorination - Lopez-Prieto, Israel J. (2022)
Different groups of disinfection by-products (DBPs) were studied through the degradation of iopamidol by the sequential oxidation process of ozone-low pressure ultraviolet light (O3-LPUV) followed by chlorination. This paper investigates the attenuation of iopamidol under this sequential treatment and the effect of chlorine contact time (30 min versus 3 days) to control the formation potential of DBPs: trihalomethanes (THMs), haloacetonitriles (HANs) and haloacetamides (HAMs). Thirty target DBPs among the 9 iodinated-DBPs (I-DBPs), were monitored throughout the sequential treatment. Results showed that O3-LPUV removed up to 99% of iopamidol, while ozone and LPUV alone removed only 90% and 76% respectively. After chlorine addition, O3-LPUV yielded 56% lower I-DBPs than LPUV. Increasing chlorine contact time resulted in higher concentrations of all DBP groups (THMs, HANs, and HAMs), with the exception of I-DBPs. One new iodinated-haloacetamide, namely chloroiodoacetamide (CIACM) and one iodoacetonitrile (IACN) were detected. These results suggest the iodine incorporated in iopamidol may be a precursor for iodinated-nitrogenous-DBPs, which are currently not well studied.